Analisa Rekonfigurasi Pembebanan Untuk Mengurangi Rugi - Rugi Daya Pada Saluran Distribusi 20 KV - S, Julen Kartoni; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
In an age of modern era of electricity has become a staple of man this is related to the level of the economy and population so that distribution of electrical energy must be guaranteed in accordance with the PP No. 5 in 2006. voltage quality and effesiensi electrical energy is strongly influenced by the voltage drop and losses - losses electrical power. Reconfiguration is one solution to overcome these problems. Feeder Bangau Sakti is one of the outgoing feeders GI Garuda Sakti with extensive feeder 51.150 kms. simulations carried out with the help of ETAP softwere (Electrical Transient Analisys Program) version 12.6. The simulation results show the lowest voltage received is 17.502 kV with a voltage drop of 14.6% to a loss of power of 1,195 MW and 1,639 MVAR. Reconfiguration is done with load transfer by means of changes in status and make changes LBS LBS layout simulation results based on ETAP 12.6 on the reconfiguration of the four lowest voltage on the feeder Bangau Sakti is 18.664 kV with loss - loss of power into 0.598 MW and 0.787 MVAR Keywords: voltage drop, power loss, reconfiguration, ETAP